Growth and Productivity of Maize (Zea mays L.) as Influenced by Precision Nutrient Management and Intercropping Cowpea (Vigna unguiculata L.) under Hot and Sub-humid Region of Odisha - Sahoo, Upasana; Malik, Ganesh Chandra; Banerjee, Mahua; Maitra, Sagar; Sairam, Masina; Bairagya, Monotoshdas (Agricultural science digest, 2024)
Background: Cereal-legume intercropping is an age-old practice in most of the countries. Among the major cereals, maize is a better choice to include in legume intercropping due to its morphology and wider row spacing. Therefore, legume intercropping in consort with proper nutrient management can enhance overall productivity of the system, further improving crop diversification, nutritional security and agriculture sustainability. Considering these aspects, the present study was performed to examine the growth and productivity of maize as influenced by precision nutrient management and cowpea intercropping. Methods: The present study was carried out during rabi season of 2022-23 at P. G. Research Farm of M.S. Swaminathan School of Agriculture, Odisha, India. The experiment was laid out in split-plot design with five intercropping combinations and five nutrient management treatments. All the treatments were replicated thrice. The plot size maintained was 5.0 m x 4.8 m. In case of maize and cowpea, high yielding hybrid ‘JKMH 4510’ and ‘KBC 9’ variety were taken for the study, respectively. Result: The results revealed that the growth parameters were significantly affected by intercropping ratios and nutrient management treatments. Although the yield attributes of maize were differed non significantly among the intercropping treatments but were significantly influenced by the nutrient treatments. In case of grain yield of maize, the Green Seeker-based nutrient management gave highest value with cowpea intercropping ratio of 1:1 and 2:2. LER and ATER were greater than unity, which indicated that the intercropping was advantageous. However, the maximum LER and Area Time Equivalent Ratio (ATER) were obtained from C3 (M+C 1:2) with 140:70:70 kg N, P2O5, K2O/ha, respectively. The study concluded that intercropping of maize + cowpea in 1:2 row ratio with Green Seeker-based nutrient management were advantageous over pure stand of maize fertilised with conventional nutrient management.